Green Marketing, Lifestyle, and the Purchase Intention of Bottled Water among Generation Z - Abid Abhirama; Nuruni Ika Khusuma Wardani; Egan Evanzha Yudha Amriel (East Asian Journal of Multidisciplinary Research, 2023)
This research aims to analyze the influence of green marketing and lifestyle on the purchase intention of Ades mineral water in Surabaya, particularly among Generation Z and millennials. The population in this study consists of consumers of packaged drinking water who are familiar with the Ades brand and are aged between 17 to 43 years. The sampling technique used to determine the sample is non-probability sampling with the purposive sampling method, involving 112 respondents. The analysis method employed is Smart PLS software with the Structural Equation Modeling (SEM) technique. The results of this study indicate that: (1) Green marketing has a positive influence on purchase intention, with a value of 0.590; (2) Lifestyle has a positive influence of 0.131 on purchase intention.